1999
DOI: 10.1110/ps.8.10.2019
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of the N‐linked glycans of HBP/CAP37/azurocidin: Crystal structure determination and biological characterization of nonglycosylated HBP

Abstract: The three N-glycosylation sites of human heparin binding protein~HBP! have been mutated to produce a nonglycosylated HBP~ng-HBP! mutant. ng-HBP has been crystallized and tested for biological activity. Complete X-ray data have been collected to 2.1 Å resolution, and the structure has been fully refined to an R-factor of 18.4%~R free 27.7%!. The ng-HBP structure reveals that neither the secondary nor tertiary structure have changed due to the removal of the glycosylation, as compared to the previously determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…3). It has been shown previously that a complete lack of glycosylation strongly reduced the biological activity of azurocidin, since the nonglycosylated protein mediated a limited stimulation of LPS-induced cytokine release from monocytes (Iversen et al, 1999). Although the lack of N-glycosylation at individual sites did not significantly influence the antibacterial activity, all these data support the hypothesis that the oligosaccharide moiety of human azurocidin may play a role in its biological function.…”
Section: Asn100supporting
confidence: 67%
See 1 more Smart Citation
“…3). It has been shown previously that a complete lack of glycosylation strongly reduced the biological activity of azurocidin, since the nonglycosylated protein mediated a limited stimulation of LPS-induced cytokine release from monocytes (Iversen et al, 1999). Although the lack of N-glycosylation at individual sites did not significantly influence the antibacterial activity, all these data support the hypothesis that the oligosaccharide moiety of human azurocidin may play a role in its biological function.…”
Section: Asn100supporting
confidence: 67%
“…This effect could be explained by the function of Asn-linked oligosaccharides in the overall protein stability and/or folding. Iversen et al (1999) showed that the lack of glycosylation did not affect the folding of azurocidin, as the secondary and tertiary structures of non-glycosylated recombinant azurocidin and wild-type recombinant azurocidin were nearly identical. The surface loops to which some glycans are attached were also unaffected by the removal of the glycosylation.…”
Section: Secretion Of Azurocidin Glycosylation Variants By Insect Cellsmentioning
confidence: 99%
“…It was negative in all cases of ALL. Azurocidin (17) and cationic antimicrobial peptides (ref. 18; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…After matching the micropreparative gel image with the analytical image, in-gel digestion was performed with a previously published protocol (17).…”
Section: Methodsmentioning
confidence: 99%
“…The putative fourth carbohydrate attachment site is located in the region between residues 89 and 114 [5]. The biological activity of HBP in regard to mediating LPS-induced IL-6 release from monocytes is severely reduced by the removal of N-glycosylation [25]. Interestingly, however, the loss of HBP glycosylation does not affect the folding, secondary and tertiary structure, or stability of HBP [25].…”
Section: Hbp Molecular Structure and Mechanismsmentioning
confidence: 99%